LEGAL INTERPRETIVISM AND SHIA LAW: A MORAL FRAMEWORK FOR REFORM - Doagoo, Hasan (My University, 2025)
This thesis investigates the reform discourse in contemporary Islamic scholarship, focusing on the contentious question of whether Islamic law requires substantial revision. Given its significant practical impact on the daily lives of Muslim communities worldwide, the inquiry centers on identifying which aspects of the legal tradition merit re-examination and determining the means by which reform may be systematically implemented. Numerous influential studies have underscored the necessity for reform and prioritized the development of a moral framework for assessing Islamic law; however, few have advanced concrete methodologies for its practical application. This research contributes to the reform discourse by proposing a moral theory of law as a viable framework for reforming Islamic legal principles. Drawing upon the well-established legal interpretivism of American legal philosopher Ronald Dworkin, the study examines the adaptability of his theory within the context of the Shia legal tradition, one of the major schools of Islamic jurisprudence. Through rigorous theoretical and practical analysis, the thesis establishes that while fundamental adaptations are required, no critical contradictions preclude the application of legal interpretivism to the Shia legal tradition. The investigation further demonstrates that a customized version of Dworkin’s theory can effectively address morally contentious perspectives inherent in Shia jurisprudence. By integrating a moral theory of law into the process of Ijtihād, the research shows how modern moral sensibilities may be incorporated into the formulation of Islamic legal opinions. The implications of this study extend beyond the confines of moral reform and Islamic law, offering a novel perspective on the interpretation and evolution of Islamic legal ideas in the modern era.
Keywords: Ronald Dworkin; Legal Interpretivism; Islamic Law; Shia law; Reform; Morality